2021
DOI: 10.1055/s-0041-1728701
|View full text |Cite
|
Sign up to set email alerts
|

Notched and Nonnotched Stimuli Are Equally Effective at the Mixing-Point Level in Sound Therapy for Tinnitus Relief

Abstract: Background Broadband noise (nonnotched) and notched noise are common sound sources in sound therapy for tinnitus relief. Studies on sound therapy using nonnotched or notched stimuli have reported large and small tinnitus improvements depending on the participant. However, the more effective sound source remains unclear given the among-study methodology differences. Purpose This study aimed to evaluate the tinnitus relief effects of sound therapy using stimuli with different spectral characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Through a randomized controlled trial, Jin et al found broadband sound stimulation still has a certain effect on alleviating tinnitus. 27 Han et al studied the tinnitus frequency matching group was significantly more effective in music therapy than the tinnitus frequency nonmatching group by running another controlled trial. 28 Therefore, we recommend that broadband music can be used, especially for patients whose tinnitus frequency is difficult to match.…”
Section: Discussionmentioning
confidence: 99%
“…Through a randomized controlled trial, Jin et al found broadband sound stimulation still has a certain effect on alleviating tinnitus. 27 Han et al studied the tinnitus frequency matching group was significantly more effective in music therapy than the tinnitus frequency nonmatching group by running another controlled trial. 28 Therefore, we recommend that broadband music can be used, especially for patients whose tinnitus frequency is difficult to match.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in this study were screened following the inclusion and exclusion criteria based on previous research on sound therapy and microcurrent stimulation for tinnitus interventions [13,14,18]. Individuals who (1) had been diagnosed with sensorineural tinnitus without signs of somatosensory tinnitus by an otolaryngologist, (2) were adults aged ≥ 20 years or older, (3) had experienced tinnitus for at least 6 months, and (4) complained of discomfort and irritation owing to tinnitus were included in this study.…”
Section: Participantsmentioning
confidence: 99%
“…The mixing point refers to the level at which the sound therapy stimulus blends with the tinnitus sound level without masking or obscuring it [19]. This study used sound therapy stimuli reported in previous studies to provide effective tinnitus relief to some participants [18]. Briefly, notched noise was created by applying a band-reject filter with a bandwidth of 1/2 octave centered at the tinnitus frequency to the broadband noise (white noise ranging from 100 to 22,050 Hz).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that sound therapy is an effective method to decrease the tinnitus-related distress, emotional reaction to and awareness of tinnitus (Kuk et al, 2010;Sweetow and Sabes, 2010;Krick et al, 2015;Liu et al, 2021). Sound therapies were initially based on broadband noise but now include noise shaped according to the audiogram (Henry et al, 2015), narrowband signals focusing on the frequency of tinnitus (Hoare et al, 2014b), notch noise (Jin et al, 2021), nature sounds (Barozzi et al, 2016;Sereda et al, 2017), music (Krick et al, 2015), or fractal tones (Tyler et al, 2017). Fractal tones are semi-randomly generated tones that sound like wind chimes.…”
Section: Introductionmentioning
confidence: 99%